The Unfinished Symphony: an evolutionary perspective on the conception of sustainable development. (1st January 2000) - Jackson, Tim
The "biophysical" critique of conventional development highlights the failure of economics to ground itself sufficiently in physical and biological realities. This paper discusses two specific aspects of modern economic systems (the profit motive and consumer behaviour), which are at best ambivalent and at worst appear actively to hinder sustainable development. Crucially, however, and in contrast to the biophysical critique, these features of the prevailing economic system find (or at least seek) a part of their justification in biological metaphors. In fact, the paper argues that there are significant metaphysical overlaps between several of the intellectual disciplines relevant to our understanding of sustainable development physics, economics, biology and psychology. Ironically, if the common scientific worldview defined by these overlaps is accepted, the prospects for achieving sustainability appear vanishingly small. On the other hand, the cultural relativity of our intellectual constructs offers some hope for revisioning the future.